PENGEMBANGAN PERANGKAT PEMBELAJARAN MELALUI PENDEKATAN RME UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH - Syahrina Anisa Pulungan; Ismi Nurul Aninda (JURNAL TEMATIK, 2020)
The purpose of this study was to find out: 1) How is the quality of learning tools developed through the RME approach in terms of validity, practicality and effectiveness, 2) How to improve students' problem-solving abilities by using learning tools developed through the RME approach. The tools developed consisted of: lesson plans, worksheets, student books (BS), learning outcomes test (THB) which were designed using the RME approach to measure the improvement in mathematical problem solving of junior high school students. This research is a development research using the Thiagarajan, Semmel and Semmel learning tools development model, namely a modified 4-D model. The results of the data analysis that have been obtained indicate that the learning device through the RME approach in the rectangular material of class VII-A SMP PAB 2 Helvetia is valid, practical and effective. For students' mathematical problem solving abilities there has been an increase